1976
DOI: 10.1111/j.1474-919x.1976.tb03516.x
|View full text |Cite
|
Sign up to set email alerts
|

THE LEVEL OF RESERVE PROTEIN AS THE PROXIMATE FACTOR CONTROLLING THE TIMING OF BREEDING AND CLUTCH‐SIZE IN THE RED‐BILLED QUELEA QUELEA QUELEA

Abstract: SUMMARY Changes in the fat and flight muscle protein reserves of adult Red‐billed Queleas Quelea quelea were followed in two colonies in Tanzania and Botswana. At the start of a breeding attempt the protein reserves were higher that at any other time of the year, particularly in females which had heavier flight muscles (non‐fat dry weight) than did the (larger) males at that time. The pre‐breeding increase in the labile component of the muscle protein (the actual protein reserve) is calculated at 80% for femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(103 citation statements)
references
References 10 publications
6
97
0
Order By: Relevance
“…Growing evidence suggests that the ecological impacts of food supplementation can depend on the specific nutritional profile of provisioned foods [48,[60][61][62][63][64] and that the energetic content of the food (in joules or calories) does not necessarily constitute an indicator of food quality [61,63]. For example, the availability of essential amino acids [62,65] and vitamins or antioxidants [60] may constrain egg production in birds. The geometric framework for nutrition (see, e.g., [66]) explores how animals simultaneously regulate the intake of multiple nutrients, and has recently been applied in birds [67].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Growing evidence suggests that the ecological impacts of food supplementation can depend on the specific nutritional profile of provisioned foods [48,[60][61][62][63][64] and that the energetic content of the food (in joules or calories) does not necessarily constitute an indicator of food quality [61,63]. For example, the availability of essential amino acids [62,65] and vitamins or antioxidants [60] may constrain egg production in birds. The geometric framework for nutrition (see, e.g., [66]) explores how animals simultaneously regulate the intake of multiple nutrients, and has recently been applied in birds [67].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…It is thus the biggest single organ within a passerines" body. Besides its main function for flight locomotion it serves as a protein source during times with high protein demands or low protein intake (Jones and Ward 1976;Piersma and Jukema 1990;Houston et al 1995;Cottam et al 2002; for review see: Piersma and Lindstöm 1997;Bauchinger and Biebach 1998;Jenni and Jenni-Eiermann 1998). The pectoral muscle generates the force for the down stroke of the wing, while the supracoracoideus muscle lifts the wing.…”
mentioning
confidence: 99%
“…Lofts & Murton 1968). This idea directed attention to non-photic cues, such as weather, temperature and food supply, and a number of studies demonstrated effects of non-photic cues on avian reproduction in tropical and xerophilous birds, as well as in 'typical' seasonal taxa of higher latitudes (reviewed by Marshall 1970; see also Ligon 1974;Jones & Ward 1976). Interest in how non-photic cues are integrated with long-term predictive cues like photoperiod has persisted (e.g.…”
Section: Diversity Of Avian Cue Response Patterns and Mechanismsmentioning
confidence: 99%